“My skills are going to be exposed” – Anxiety, meaning and professional identity during simulation-based learning in medical students: A mixed method study - Gareth Drake; Niki Skaltsa; Kritika Kalia; Chibueze Ogbonnaya; Asha Padhair; Samuel Morrish; Pratheeban Nambyiah (PLoS ONE, 2025)
Clinical simulation is an established part of the educational offering for healthcare workers, yet for many it can induce feelings of anxiety and uncertainty. The role of these feelings in enhancing or impeding the pedagogical experience is unclear, but it is likely that there are mediating and moderating factors that affect the relationship. We undertook a prospective, observational, mixed methods study of a cohort of medical students undergoing a paediatric critical illness simulation course. Our quantitative aims were to understand whether increased state anxiety correlated negatively with simulation effectiveness. Our qualitative aim was to understand how students experienced their anxiety in relation to their learning experience during the simulation. We found that there was no significant relationship between state anxiety and simulation effectiveness. However, during qualitative interviews, we uncovered a rich seam of material regarding the students’ experience which coalesced around three broad themes – anticipation of the unknown, the nature of being observed, and the realism of clinical simulation, which elicited reflections among students on their future professional responsibilities and identity. We found that these feelings were simultaneously triggers for anxiety – and we suggest some practical ways of reducing the stress associated with this – and also the gateway to great insight for students into their learning process. Traditionally, learning in medicine has been associated with a maladaptive culture of perfection – high academic expectations, the perception that the ability to recall under pressure is the hallmark of a good doctor, and unwillingness to admit to vulnerability or error. Simulation leads students to the understanding that successful performance in real clinical settings requires asking for help, recognising the demands on and the limitations of available resources, and being able to navigate uncertainty.